2021
DOI: 10.1093/ejcts/ezaa333
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-cancer death after surgery in patients with stage I non-small-cell lung cancer

Abstract: OBJECTIVES With improvements in the outcome of treatment for non-small-cell lung cancer (NSCLC), other diseases may account for a high death rate after surgery in patients with stage I NSCLC. In the present study, we analysed the associations between the clinical factors and non-cancer death after surgery in these patients. METHODS The records of 514 patients with stage I NSCLC who underwent surgery were retrospectively revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, these patients often have reduced tolerance to surgical intervention. Thus, it is critical to consider factors, such as age, body mass index (BMI), performance status, smoking status, comorbidities, and the presence of sarcopenia, when determining the course of treatment (Leduc et al 2017; Kanzaki et al 2021; Kawaguchi et al 2010; Kravchenko et al 2015;Nakamura et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, these patients often have reduced tolerance to surgical intervention. Thus, it is critical to consider factors, such as age, body mass index (BMI), performance status, smoking status, comorbidities, and the presence of sarcopenia, when determining the course of treatment (Leduc et al 2017; Kanzaki et al 2021; Kawaguchi et al 2010; Kravchenko et al 2015;Nakamura et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the behaviour of the nodal spread in these patients might improve our capability to offer a radical treatment, even in these aggressive forms. On the other hand, prospective investigations assessing the possibility of more limited nodal resection in early-stage NSCLC might help reduce the rate of complications and postoperative morbidity [ 26 , 27 ]. Finally, even higher detection rates could be reached by switching from the one-dimensional exploration capability afforded by the gamma-probe to the 2D imaging offered by portable gamma cameras [ 28 ] or even to 3D, in vivo representation of sentinel nodes following pre-operative SPECT imaging, which has been suggested in many surgical fields [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also revealed that the cancer-specific survival of patients who climbed < 18 m was worse than that of patients who climbed > 18 m. Our study suggests that patients who could not complete the MDT tended to have worse overall survival, and those patients are more likely to die from diseases other than cancer. Kanzaki et al revealed that age (≥ 70), male sex, body mass index (< 18.5 kg/m 2 ), postoperative complications and low preoperative % forced expiratory volume 1 (< 80) were risk factors for postoperative non-cancer death after surgery in patients with stage I NSCLC [ 19 ]. Their results are reflected by the frailty of the patients who could not complete the MDT.…”
Section: Discussionmentioning
confidence: 99%